Pengaruh Pengetahuan Investasi, Motivasi Investasi dan Literasi Keuangan Terhadap Minat Investasi di Pasar Modal - Rizal Fauzan Adhima; Carolyn Lukita; Thomas Nadeak (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to determine the influence of investment knowledge, investment motivation and financial literacy on investment interest in the market. This research uses three independent variables and one dependent variable. Independent variables: investment knowledge (X1), investment motivation (X2), and financial literacy (X3). With the dependent variable investment interest (Y). The data used in this research is secondary quantitative data obtained from distributing questionnaires via Google Form. This research is secondary quantitative research. The time for distributing the questionnaire from December 2023 to January 2024 was 110 pieces of data. This research uses multiple linear analysis. Hypothesis testing is carried out using partial regression tests and simultaneous tests. The results of this research are that the influence of investment, investment motivation and financial literacy influence investment interest.